Nuevas Viñetas. - Cava, Felipe Hernandez; Ceder, Michel; Soliman, Magdy Martinez; Ministerio de Cultura, Madrid (Madrid : Museo Espanol de Arte Contemporaneo, 1990)
Bernabeu, Rafael ; Castells, Ricard ; Corcuera, Juan Luis ; Entrialgo, Mauro ; Flores, Enrique ; Gras, Jesus ; Hidalgo, Manuel ; Nguema, Manuel ; Olivares, Javier ; Pelegrin, Eduardo ; Atonito, Romance ; Tamayo, Alfons ; Vazquez, Javier ; Cifre, Guillem ; Giandelli, Gabriella ; Micharmut ; Mokka, Grupo
Nuevas Viñetas, Museo Espanol de Arte Contemporaneo (MEAC), Madrid, 1 de agosto al 30 de septiembre de 1990
biografie
Spaans
kunstcatalogus